Perspectivas dos docentes de pós-graduação: uma análise do trabalho de orientação acadêmica em um programa de pós-graduação da área da biodiversidade de uma universidade pública de Mato Grosso - Sousa, Geyce Martins de Alencar (Universidade Federal de São Carlos, 2024)
This study investigates the perceptions of faculty members in a Graduate Program, aiming to analyze faculty perception regarding their work in graduate studies, especially concerning the scientific guidance of students, as well as to discuss possible influences of evaluation criteria established by CAPES (Coordination for the Improvement of Higher Education Personnel) in this context. Faculty work encompasses cross-cutting demands of affective, social, political, cultural, and economic nature. It is an activity in which professional experience and human interaction stand out in its execution. In this context, one of the aspects of faculty work is academic research guidance, which in turn encompasses dimensions that confer a high degree of complexity and supports scientific production with the participation of students and graduates in graduate programs. To deepen the understanding of the subject, a case study was conducted based on theoretical frameworks of Activity Ergonomics. This is a descriptive research with a qualitative approach, focused on understanding aspects of human behavior and their meanings related to the perception, experience, and opinion of the guiding subjects themselves. Data collection involved document analysis and the application of questionnaires and interviews. The data obtained through document analysis and the questionnaire were exploratory, providing an initial and comprehensive view of the topics covered. Interviews allowed for a more detailed and in-depth exploration of participants' perceptions, experiences, and viewpoints. Thematic content analysis approach was employed for the analysis of interviews, leading to the emergence of three themes encompassing the categories of research findings: perceptions about faculty work in graduate studies, difficulties faced, and strategies used in this work context. The findings of this study indicated that prior teaching experience as a mentee is the main element guiding mentoring work. The tasks prescribed in the context of work are broad and unfold into various activities, often resulting in overload. Guidance, for example, involves the development of research projects, seeking financial resources, and attention to psycho-emotional aspects, among other underlying responsibilities. Despite the challenges, it is a rewarding role due to the opportunity to positively influence the formation of future professionals in the field of knowledge. In this context, improving students' autonomy and commitment is seen as a promising opportunity to reduce situations of strain and overload.
Perspectives of postgraduate teachers: an analysis of academic guidance work in a postgraduate program in the area of biodiversity at a public university of Mato Grosso
Keywords: Trabalho docente; Pós-graduação; Avaliação; Orientação; ENGENHARIAS::ENGENHARIA DE PRODUCAO